Post-quantum-inspired scalable blockchain architecture for internet hospital systems with lightweight privacy-preserving access control - Lulu Hao; Ruoyu Wang; Xiaofeng Wang; Xiaoguang Yue; Noshina Tariq; Ahthasham Sajid (PLoS ONE, 2025)
The increasing adoption of Internet hospital systems—enabled by the real-time data streaming capabilities of the Internet of Medical Things (IoMT)—has intensified the need for secure, scalable, and low-latency data management infrastructures. Existing blockchain-based solutions often fail to meet these requirements, particularly under high-frequency workloads and stringent privacy demands. To address these limitations, this study proposes a simulation-based post-quantum-inspired alliance blockchain architecture tailored for Internet hospital systems. The framework incorporates four key innovations: (1) a Kyber-inspired hybrid encryption simulation, reducing encryption and decryption times by 72.3% and 74.4%, respectively, compared to RSA-2048; (2) a lightweight patient-centric access control mechanism based on authorization proofs achieving an average verification latency of ∼0.002 ms; (3) a Raft-based scalable consensus protocol, tested under a synchronous constant-delay network assumption, reducing consensus latency by 92.3% while supporting up to 1000 nodes with sub-150 ms finality; and (4) a fault-tolerant IoMT data ingestion layer using 3-of-5 median filtering, sustaining 90–96.2% sensor correction accuracy under varying fault injection rates. The system is prototyped in Google Colab Pro using synthetic data from 1000 virtual patients. Comparative benchmarks against PBFT and RSA-based systems show a fivefold increase in throughput, ∼9.4–12.3% energy savings per transaction, and ∼14% lower memory consumption during encryption. With a modest daily storage footprint (∼15 MB/day), the proposed solution is both resource-efficient and deployment-ready in simulation environments. These results confirm the potential of this architecture to enable trustworthy, energy-aware, and real-time blockchain infrastructures for next-generation digital healthcare ecosystems.